HUBUNGAN PENGETAHUAN IBU BALITA TENTANG GIZI BALITA DENGAN STATUS GIZI BALITA DI KELURAHAN BINTUJU KECAMATAN BATANG ANGKOLA TAHUN 2016 - pohan, rostina afrida; siregar, yuli arisyah (Universitas Aufa Royhan, 2016)
The goal of the research to know the correction of the mothers aboot infant nutrition withnutritional status of children in the village bintuju kecamatan batang angkola the research is descriptifcorrection. Population in this study are all mothers who have children that wiht total sampling techniquestudied by the relation ship of know ledge mothers with infant nutritional status processed data editing ,cooding, ang tabulation analyzed and collected in the table ang continued to discuss the resuit of thestudy.The resuit of the research revealed that the caracteristic of the mayority aged 20-35 years as manyas 13 people (43,3%), the mayority of educated ase junior high school SMP. And the working as a selfemployed 14 people (46,7%), and the mayority know ledgeabel enough as many as 20 people. And the asmany mayority infant wiht adequate nutrition status of as many as 24 people. After data in the analysis of30 respondents based on a statistical test of knowledge and nutritional status variabels using the chisquaretest was obtained p = 0,074 (>0,05) means thae there is no correlation between knowledge ofmothers whit infant nutritional status, than Ho accepted and Ha rejected.